Change-of-state paradigms and the middle in Kinyarwanda. Issue 3 (10th December 2018) - Jerro, Kyle
Abstract: This article investigates the derivational relationships among members of verbal paradigms in Kinyarwanda (Bantu JD61; Rwanda) by pursuing two interrelated goals. First, I describe a variety of derivational strategies for marking transitive and intransitive variants in change-of-state verb paradigms. Second, I focus on the detransitivising morpheme -ik which serves as one possible marking for intransitive members of these paradigms. Ultimately, I argue that this morpheme is a marker of middle voice, and the variety of readings which appear with this form can be subsumed under a single operation of argument suppression. Finally, I provide a discussion of reflexives and the apparent lack of a reflexive reading with -ik by arguing that this reading is blocked by either lexical reflexives or the reflexive prefix i-.